Characteristics of Coping Strategy in Strengthening Stress Stability in Students - Zuhuriddinovna, Ismoilova (Indonesian Journal Publisher, 2025)
Today’s intense processes place a huge responsibility on the modern student personality. We know that studentship is not only a “golden age” of human life, but also a time when one is exposed to a number of stressogenic factors related to daily and academic activities. Problems and obstacles for the student's body and psyche to learn a new social environment, new requirements, new values or the reconstruction of this system, the emergence of new needs, their satisfaction - all this can be a factor of serious stress for the student. But each student perceives a certain situation differently depending on their individual, personal, cognitive characteristics, which determines his level of resistance to stress. A student’s perception of changes in his or her life not as a threat to himself or herself, but as a quality of developmental opportunity, and treating them with openness and interest are among the characteristics that ensure his or her resilience to stress. In order to accurately analyze the extent to which these features are affected, of course, special psychological research is required. This article presents and analyzes the results of an empirical study of the role of coping strategies in modern student attitudes toward stress, in particular the national psychological features of the relationship between problem solving, seeking social support, and problem avoidance strategies and stress resilience.